Uma arquitetura para otimização do acesso em redes em malha sem fio - Gleicy Aparecida Cabral (2008)
Wireless mesh networks are dynamically self-organized and self-configured, with the nodes in the network automatically establishing and maintaining mesh connectivity among themselves. Wireless mesh networks consist of three types of nodes: clients, routers and gateways. Routers have minimal or no mobility. Routers form the backbone of mesh networks. Multi-hop communication is used in wireless mesh network and the gateway/bridge functionalities in nodes enable the integration of wireless mesh networks with various existing wireless networks such as Internet, Wi-Fi, cellular, etc.Wireless mesh networks planning involves several variables as network topology, mobility, traffic, cost and capability. This paper presents a mathematical model for the planning of wireless mesh networks. The model solution determines the routes between clients and gateways that minimize the installation costs of the routers and the costs of links that are part of the routes. Experiments are conducted for model evaluation using optimization software CPLEX. Experiments show that the planning of wireless mesh networks is a computationally difficult problem. In this work is also developed a simulator for wireless mesh networks over the simulation frameworks JiST and SWANS. The proposed routing algorithm finds routes that also minimize the installation costs of the routers and the costs of links that are part of the routes. The simulation solutions are compared with the solutions found by CPLEX. The simulator is robust and efficient. It finds good solutions and it is able to simulate large networks.